Molybdenum-containing heat-conducting austenitic manganese steel and preparation method thereof

By introducing molybdenum element into manganese steel and using laser cladding technology to form a nickel-based and aluminum nitride composite powder cladding layer, the problem of poor thermal conductivity of manganese steel is solved and its thermal conductivity, thermal stability and oxidation resistance are improved.

CN119332158AActive Publication Date: 2025-01-21JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411885774.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When the manganese content increases, the thermal conductivity of manganese steel decreases, and the thermal conductivity is poor. It is easy to form internal stress during rapid heating or cooling, causing cracking of parts, and the heat is not easy to be exported, which is prone to thermal deformation, affecting thermal processing.

Method used

Using austenitic manganese steel containing molybdenum element and its preparation method, pig iron and pure iron are mixed and smelted, ferrochromium, ferromanganese, ferromolybdenum, etc. are added to form molten steel, and then heat treatment is performed to form austenitic manganese steel. And a nickel-based cladding layer and an aluminum nitride composite powder cladding layer are formed on the surface through laser cladding technology to improve thermal conductivity.

Benefits of technology

It improves the thermal conductivity of manganese steel, improves its thermal stability and oxidation resistance, reduces the risk of thermal deformation of parts at high temperatures, and enhances its wear resistance, corrosion resistance and high temperature oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses heat-conducting austenitic manganese steel containing a molybdenum element and a preparation method of the heat-conducting austenitic manganese steel, and relates to the technical field of molybdenum-containing manganese steel. Ferrochromium, ferromanganese, ferromolybdenum, ferrotitanium, ferrocolumbium and chromium nitride are added, smelting continues, and molten steel is formed; discharging and pouring to obtain a blank; and performing heat treatment to obtain the austenitic manganese steel. According to the method, the element molybdenum is added into the manganese steel to form carbides with carbon in the manganese steel, and the carbides are dispersed and distributed in the steel, so that the form and distribution of the carbides in the austenitic manganese steel can be optimized, defects in the manganese steel are reduced, dislocation motion is inhibited, and the heat conductivity of the manganese steel is improved; meanwhile, surrounding solute atoms are depleted, so that the heat conductivity can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molybdenum-containing manganese steel, in particular to a thermally conductive austenitic manganese steel containing molybdenum element and a preparation method thereof. Background Art

[0002] ‌Manganese steel is a high-strength steel, the main features of which are its high strength, high hardness and good wear resistance. As a traditional wear-resistant steel, manganese steel has a wear resistance that is unmatched by other materials in terms of resisting abrasive wear or chiseling wear under strong impact and high stress. In addition, manganese steel also has good toughness and corrosion resistance, showing good tensile strength, impact resistance and wear resistance, and is suitable for various high-intensity working environments. Due to its high strength and wear resistance, manganese steel performs well in these fields and can withstand greater pressure and wear. The application field of manganese steel is very wide, and it is often used to manufacture mechanical parts, automobile parts, railway vehicles, bridges, excavators, loaders and other equipment. However, with the increase of manganese content, the thermal conductivity of manganese steel drops sharply and the thermal conductivity is poor; the linear expansion coefficient increases, and large internal stress will be formed when it is quickly heated or cooled, and the cracking tendency of parts increases; and the heat is not easy to be discharged during processing, and thermal deformation is easy to occur, which is not conducive to hot processing of manganese steel. Therefore, we propose a thermally conductive austenitic manganese steel containing molybdenum and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a thermally conductive austenitic manganese steel containing molybdenum and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Mix pig iron and pure iron and smelt them together; add ferrochrome, ferromanganese, ferromolybdenum, ferrotitanium, ferroniobium and chromium nitride and continue smelting to form molten steel; pour out of the furnace and cast to obtain billet; perform heat treatment to obtain austenitic manganese steel.

[0005] Furthermore, austenitic manganese steel includes the following mass components: carbon (C): 1.2-1.5%, manganese (Mn): 6-9%, molybdenum (Mo): 1-2%, chromium (Cr): 2-4%, silicon (Si): 0.8-1.0%, nitrogen (N): 0.1-0.5%, titanium (Ti): 0.06-0.10%, niobium (Nb): 0.05-0.07%, phosphorus (P) ≤0.07%, sulfur (S) ≤0.04%, and the balance is iron (Fe).

[0006] Furthermore, the smelting temperature is between 1420 and 1480°C.

[0007] Furthermore, the chromium nitride is added at a temperature of 1550-1570° C., and then smelting is continued for 40-60 minutes.

[0008] Furthermore, the furnace temperature is 1520-1550°C, and the pouring temperature is 1370-1420°C.

[0009] Furthermore, the process conditions of the heat treatment are: heating to 1080-1130° C. and keeping warm for 90-100 minutes.

[0010] Furthermore, the heat treatment process is: firstly, heating to 650-700℃ at a heating rate of 50-100℃ / h, keeping warm for 1-3h; then heating to 1050-1110℃ at a heating rate of 100-150℃ / h, keeping warm for 90-100min; then water cooling, the water temperature is 10-20℃, and the water temperature after water cooling is ≤45℃. The austenite transformation of manganese steel occurs, and its toughness is improved.

[0011] In the above technical solution, chromium (Cr) in manganese steel can combine with elemental carbon in steel to form hard carbide, thereby improving the hardness and wear resistance of manganese steel, making it more suitable for various working conditions. Chromium can also form a dense oxide film on the surface of steel, preventing direct contact between oxygen and moisture and the steel matrix, thereby improving the corrosion resistance of manganese steel, making it suitable for use in humid and corrosive environments.

[0012] The element molybdenum (Mo) is a strong carbide-forming element. It can form carbides with carbon in manganese steel and disperse in the steel. It can optimize the morphology and distribution of carbides in austenitic manganese steel, reduce defects in manganese steel, and inhibit dislocation movement, which helps to improve the thermal conductivity of manganese steel; at the same time, the solute atoms around it are depleted, which can further improve its thermal conductivity. Molybdenum carbides have a high melting point and hardness, and can fix other carbides in manganese steel to a certain extent, inhibit cementite aggregation, promote carbides to disperse in small sizes, strengthen the austenite structure of manganese steel, and improve its hardness and strength. This helps to improve the wear resistance of manganese steel, reduce its damage under friction and wear, and has good thermal stability, mechanical stability and corrosion resistance. At high temperatures, molybdenum can form a stable solid solution with iron, thereby improving the high-temperature strength and plasticity of manganese steel and improving its thermal properties. However, if the molybdenum content in manganese steel is too high, it will be dissolved in the steel matrix after heat treatment. Due to the large size difference between it and iron atoms, it will produce a huge polar potential, causing lattice distortion, and reducing grain boundary strengthening effect and impact toughness; the scattering effect of electrons is enhanced, and thermal conductivity is reduced, which is not good for the comprehensive performance of manganese steel.

[0013] The addition of silicon can refine the grains, improve the hardness and wear resistance of manganese steel, and improve its thermal stability and oxidation resistance. A small amount of nitrogen, which mainly exists in the form of nitrides in manganese steel, can improve the hardness and strength of the steel, improve its wear resistance and corrosion resistance, and make it more adaptable to various working conditions. It can also improve its plasticity and toughness, and enhance the impact resistance of manganese steel. However, excessive nitrogen will cause the plasticity and toughness of steel to decrease, and easily cause brittle fracture. Niobium can exist in the blank in the form of carbides, improving its hardness and toughness; after heat treatment, it is partially melted in austenitic manganese steel, which can inhibit the growth of organizational grains and improve its hardenability. Austenitic manganese steel can obtain higher hardness and improved wear resistance.

[0014] Furthermore, after the heat treatment, molybdenum infiltration and vapor deposition are sequentially performed to form a molybdenum layer; The process conditions of molybdenum diffusion are: inter-electrode spacing 18mm, source voltage 650V, source current 1.4~1.6V, cathode voltage 400V, cathode current 3.8~4.0A, temperature 940~960℃, atmosphere is argon, working pressure 35Pa, source is pure molybdenum, sputtering for 1~3h; sputtering without passive electrode under mask for 30~90min; The process conditions of vapor deposition are: using molybdenum hexafluoride and hydrogen as raw materials, the deposition temperature is 1000-1100°C, the pressure is 2.0-2.7 kPa, and the duration is 90-120 minutes.

[0015] Furthermore, after vapor deposition, the alloy powder is taken to perform laser cladding on austenitic manganese steel to form a cladding layer; The process conditions of laser cladding are: laser power 1150~1250W, scanning speed 3.5~4.5mm / s, powder feeding speed 7.0~8.0g / min; laser spot diameter 1.5mm, overlap rate 60%, defocus amount 15mm, powder feeding gas and shielding gas are argon.

[0016] Furthermore, the thickness of the cladding layer is 1.5 to 2.0 mm.

[0017] Furthermore, the alloy powder is a Ni60 alloy powder of 45 to 106 μm and an aluminum nitride composite powder, with a volume ratio of (5 to 7): (3 to 5); Before use, dry at 150℃ for 60min to remove moisture.

[0018] Furthermore, the Ni60 alloy powder includes the following mass components: carbon 0.6-1.0%, silicon 3.0-4.5%, chromium 14-17%, boron 2.5-4.5%, iron <15%, lanthanum 0.04-0.07%, and the balance is nickel.

[0019] Furthermore, before laser cladding, the austenitic manganese steel was preheated at 150 °C for 60 min.

[0020] In the above technical scheme, the alloy powder is melted in the flight space by laser cladding technology, a micro-molten pool is formed on the surface of austenitic manganese steel, the alloy liquid forms a metallurgical bond with the manganese steel, and a cladding layer is formed. The overall dendrite structure is fine, the difference in intercrystalline composition is small, the grain distribution is uniform, and there are hard borides and carbides in the structure. The addition of rare earth lanthanum makes the compound finer and dispersed, which can inhibit the segregation of harmful impurities on the grain boundary, reduce the brittleness of the structure, and alleviate the performance gradient difference between the cladding layer and the manganese steel matrix. It can effectively improve the surface hardness of the matrix, and has good wear resistance, corrosion resistance, and high-temperature oxidation resistance. The surface roughness of the nickel-based cladding layer is low, and the machining amount of the parts after cladding is reduced; the thermal conductivity of metal nickel is better. When it is set on the surface of manganese steel as a cladding layer, it can flatten the surface and remove the oxide layer; it can also reduce heat accumulation, optimize heat distribution, promote rapid conduction and uniform distribution of temperature, and alleviate local overheating, thereby effectively improving the overall thermal conductivity of manganese steel.

[0021] By using aluminum nitride composite powder as raw material, the cladding layer contains aluminum nitride. Aluminum nitride has extremely high thermal conductivity and hardness, which can further enhance the hardness and thermal conductivity of the cladding layer, and the overall thermal conductivity and wear resistance of manganese steel are greatly promoted.

[0022] Preheating the workpiece (austenitic manganese steel) can slow down the temperature gradient, relieve stress concentration, and reduce the cracking tendency of the cladding layer. The relatively high scanning speed and powder feeding rate can reduce the maximum temperature during the laser cladding process, thus helping to obtain better performance of the cladding layer.

[0023] In the above technical solution, plasma metal infiltration technology is used to infiltrate molybdenum on the surface of manganese steel to form an alloy layer rich in metallic molybdenum on its surface, which can effectively improve the hardness and wear resistance of manganese steel and help improve its corrosion resistance. Then, passive polar sputtering is performed to pattern the surface of the alloy layer to form gullies. Then, molybdenum hexafluoride is used as a molybdenum source, and chemical vapor deposition is performed under the reduction action of hydrogen. Metallic molybdenum is generated and deposited under high temperature and high pressure. Molybdenum elements migrate and expand and grow from the alloy layer to the gully, thereby forming a molybdenum layer with interface voids, which can promote the disappearance of dislocations and stress release. In laser cladding, molybdenum is dissolved in nickel, further improving the corrosion resistance and high temperature resistance of the cladding layer; at the same time, the interface voids can partially migrate to the cladding layer to form relatively diffusely distributed nanopores, which helps to relieve stress concentration, inhibit the initiation of cracks, promote the interaction between the surface and dislocations, improve its strength and plasticity, and retain the thermal conductivity of the manganese steel matrix and its surface.

[0024] Furthermore, the aluminum nitride composite powder is prepared by the following process: Aluminum nitride, titanium powder and copper powder are mixed, vacuum ball milled at 200-250 r / min for 10-12 hours, and then spark plasma sintered. The sintering temperature is 950-970°C, the heating rate is 100°C / min, the loading pressure is 50 MPa, and the sintering time is 10-12 minutes.

[0025] Further, the volume ratio of aluminum nitride, titanium powder, and copper powder is 100: (4.5-8.0): (90-110); The particle sizes of aluminum nitride, titanium powder and copper powder are between 2 and 30 μm.

[0026] In the above technical scheme, active titanium elements and copper can generate TiN and CuTi phases on the surface of aluminum nitride to form an interface layer, thereby realizing the interface bonding between aluminum nitride and copper, which is conducive to the composite between aluminum nitride and copper. The deformation difficulty of the composite material is increased, the fatigue resistance of the prepared cladding layer and its interface with the manganese steel substrate is improved, the sensitivity to temperature is reduced, and the hardness is increased. Moreover, copper and titanium both have high thermal conductivity, which is conducive to the comprehensive improvement of the wear resistance and thermal conductivity of the manganese steel surface. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Pig iron includes: by mass, carbon: 3.0%, manganese: 0.27%, silicon: 0.01%, phosphorus 0.035%, sulfur 0.03%, the balance is iron; pure iron: purity ≥ 99.9%; ferrochrome: chromium: 70%, carbon: 0.25%, silicon: 2.0%, the balance is iron; ferromanganese: manganese: 80%, carbon: 1.5%, silicon: 1.5%, the balance is iron; ferromolybdenum: molybdenum: 60%, carbon: 0.1%, silicon: 1.0%, the balance is iron; ferrotitanium: titanium: 70%, aluminum: 0.5%, silicon: 0.3%, the balance is iron; ferroniobium: niobium: 70%, carbon: 0.03%, silicon: 0.15%, the balance is iron; chromium nitride: purity ≥ 99.6%, silicon: 1.0%, the balance of iron ≤ 0.35%; The molten steel composition includes the following components: by mass, carbon: 1.35%, manganese: 7.54%, molybdenum: 1.35%, chromium: 3.70%, silicon: 0.98%, nitrogen: 0.18%, titanium: 0.08%, niobium: 0.06%, phosphorus 0.045%, sulfur 0.01%, and the balance is iron; Ni60 alloy powder includes the following mass components: carbon 0.8%, silicon 4.0%, chromium 16.0%, boron 4.0%, iron 8.0%, lanthanum 0.06%, and the balance is nickel; the particle size range is 45 to 105 μm, and the average particle size is 57 μm; Aluminum nitride, titanium powder, copper powder: purity ≥99.9%, particle sizes are 25μm, 1μm, 15μm respectively; source pure molybdenum: purity ≥99.99%.

[0029] Embodiment 1: A method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Step 1, mixing pig iron and pure iron, smelting at a temperature of 1420°C; adding ferrochrome, ferromanganese, ferromolybdenum, ferrotitanium, ferroniobium and chromium nitride, the adding temperature of chromium nitride is 1550°C, and then continuing to smelt for 40 minutes to form molten steel; taking out of the furnace, the taking out of the furnace temperature is 1520°C, pouring, the pouring temperature is 1370°C, and obtaining a billet; Heat treatment, the process conditions are: firstly heating to 650℃ at a heating rate of 50℃ / h, keeping the temperature for 1h; then heating to 1050℃ at a heating rate of 100℃ / h, keeping the temperature for 90min; then water cooling, the water temperature is 10℃, and the water temperature after water cooling is 40℃, to obtain austenitic manganese steel; Step 2: Using pure molybdenum as the source electrode, molybdenum is infiltrated on austenitic manganese steel. The process conditions are: inter-electrode spacing 18 mm, source voltage 650 V, source current 1.4 V, cathode voltage 400 V, cathode current 3.8 A, temperature 940 ° C, argon atmosphere, working pressure 35 Pa, source electrode is pure molybdenum, after sputtering for 1 hour; sputtering without source electrode is performed under the mask for 30 minutes; Then, molybdenum hexafluoride and hydrogen were used as raw materials for vapor deposition. The process conditions were: deposition temperature of 1000°C, pressure of 2.0 kPa, and duration of 90 min. Step 3, aluminum nitride, titanium powder and copper powder are mixed, vacuum ball milled at 200 r / min for 10 hours, and then spark plasma sintered, the sintering temperature is 950° C., the heating rate is 100° C. / min, the loading pressure is 50 MPa, and the sintering time is 10 minutes; the volume ratio of aluminum nitride, titanium powder and copper powder is 100:4.5:110; The alloy powder is used to perform laser cladding on austenitic manganese steel to form a cladding layer, thereby obtaining a manganese steel material; the alloy powder is Ni60 alloy powder and aluminum nitride composite powder, and the volume ratio is 7:3; before use, it is dried at 150°C for 60 minutes to remove moisture; before laser cladding, the austenitic manganese steel is preheated at 150°C for 60 minutes; The process conditions of laser cladding are: laser power 1150W, scanning speed 3.5mm / s, powder feeding speed 7.0g / min; laser spot diameter 1.5mm, overlap rate 60%, defocus amount 15mm, powder feeding gas and protective gas are argon.

[0030] Embodiment 2: A method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Step 1, mixing pig iron and pure iron at a temperature of 1450°C and smelting; adding ferrochrome, ferromanganese, ferromolybdenum, ferrotitanium, ferroniobium and chromium nitride, the addition temperature of chromium nitride is 1560°C, and then continuing to smelt for 50 minutes to form molten steel; taking out of the furnace, the furnace temperature is 1540°C, pouring, the pouring temperature is 1400°C, and obtaining a billet; heat treatment, the process conditions are: first heating to 680°C at a heating rate of 75°C / h, and keeping warm for 2h; then heating to 1080°C at a heating rate of 120°C / h, and keeping warm for 95min; then water cooling, the water temperature is 15°C, and the water temperature after water cooling is 40°C, to obtain austenitic manganese steel; Step 2: Using pure molybdenum as the source electrode, molybdenum is infiltrated on austenitic manganese steel. The process conditions are: inter-electrode spacing 18 mm, source voltage 650 V, source current 1.5 V, cathode voltage 400 V, cathode current 3.9 A, temperature 950 ° C, atmosphere argon, working pressure 35 Pa, source electrode is pure molybdenum, after sputtering for 2 hours; sputtering without source electrode is performed under the mask for 60 minutes; Then, molybdenum hexafluoride and hydrogen were used as raw materials for vapor deposition. The process conditions were: deposition temperature of 1050°C, pressure of 2.4 kPa, and duration of 100 min. Step 3, aluminum nitride, titanium powder and copper powder are mixed, vacuum ball milled at 220 r / min for 11 hours, and then spark plasma sintered, the sintering temperature is 960°C, the heating rate is 100°C / min, the loading pressure is 50 MPa, and the sintering time is 11 minutes; the volume ratio of aluminum nitride, titanium powder and copper powder is 100:6:100; The alloy powder is used to perform laser cladding on austenitic manganese steel to form a cladding layer, thereby obtaining a manganese steel material; the alloy powder is Ni60 alloy powder and aluminum nitride composite powder, and the volume ratio is 6:4; before use, it is dried at 150°C for 60 minutes to remove moisture; before laser cladding, the austenitic manganese steel is preheated at 150°C for 60 minutes; The process conditions of laser cladding are: laser power 1200W, scanning speed 4.0mm / s, powder feeding speed 7.5g / min; laser spot diameter 1.5mm, overlap rate 60%, defocus amount 15mm, powder feeding gas and protective gas are argon.

[0031] Embodiment 3: A method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Step 1, mixing pig iron and pure iron at a temperature of 1480°C and smelting; adding ferrochrome, ferromanganese, ferromolybdenum, ferrotitanium, ferroniobium and chromium nitride, the addition temperature of chromium nitride is 1570°C, and then continuing to smelt for 60 minutes to form molten steel; taking out of the furnace, the furnace temperature is 1550°C, pouring, the pouring temperature is 1420°C, and obtaining a billet; heat treatment, the process conditions are: first heating to 700°C at a heating rate of 100°C / h, and keeping warm for 3h; then heating to 1110°C at a heating rate of 150°C / h, and keeping warm for 100min; then water cooling, the water temperature is 20°C, and the water temperature after water cooling is 40°C, to obtain austenitic manganese steel; Step 2: Using pure molybdenum as the source electrode, molybdenum is infiltrated on austenitic manganese steel. The process conditions are: inter-electrode spacing 18 mm, source voltage 650 V, source current 1.6 V, cathode voltage 400 V, cathode current 4.0 A, temperature 960 ° C, argon atmosphere, working pressure 35 Pa, source electrode is pure molybdenum, after sputtering for 3 hours; sputtering without source electrode is performed under the mask for 90 minutes; Then, molybdenum hexafluoride and hydrogen were used as raw materials for vapor deposition. The process conditions were: deposition temperature of 1100°C, pressure of 2.7 kPa, and duration of 120 min. Step 3, aluminum nitride, titanium powder and copper powder are mixed, vacuum ball milled at 250 r / min for 12 hours, and then spark plasma sintered, the sintering temperature is 970°C, the heating rate is 100°C / min, the loading pressure is 50 MPa, and the sintering time is 12 minutes; the volume ratio of aluminum nitride, titanium powder and copper powder is 100:8:110; The alloy powder is used to perform laser cladding on austenitic manganese steel to form a cladding layer, thereby obtaining a manganese steel material; the alloy powder is Ni60 alloy powder and aluminum nitride composite powder, and the volume ratio is 5:5; before use, it is dried at 150°C for 60 minutes to remove moisture; before laser cladding, the austenitic manganese steel is preheated at 150°C for 60 minutes; The process conditions of laser cladding are: laser power 1250W, scanning speed 4.5mm / s, powder feeding speed 8.0g / min; laser spot diameter 1.5mm, overlap rate 60%, defocus amount 15mm, powder feeding gas and shielding gas are argon.

[0032] Comparative Example 1: A method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Step 2: Using pure molybdenum as the source, molybdenum is infiltrated on austenitic manganese steel. The process conditions are: inter-electrode spacing 18 mm, source voltage 650 V, source current 1.4 V, cathode voltage 400 V, cathode current 3.8 A, temperature 940 ° C, atmosphere argon, working pressure 35 Pa, source is pure molybdenum, and sputtering is 1 h. Step 1 and step 3 are the same as those in Example 1 to obtain a manganese steel material.

[0033] Comparative Example 2: A method for preparing thermally conductive austenite containing molybdenum element, wherein step 1 and step 2 are the same as step 1 and step 3 in Example 1 to obtain a manganese steel material.

[0034] Comparative Example 3: A method for preparing thermally conductive austenite containing molybdenum, comprising the following process: Step 2, taking Ni60 alloy powder to perform laser cladding on austenitic manganese steel to form a cladding layer to obtain a manganese steel material; before laser cladding, the austenitic manganese steel is preheated at 150° C. for 60 minutes; The process conditions of laser cladding are as follows: laser power 1150W, scanning speed 3.5mm / s, powder feeding speed 7.0g / min; laser spot diameter 1.5mm, overlap rate 60%, defocusing amount 15mm, powder feeding gas and shielding gas are both argon; Step 1 is the same as that in Example 1 to obtain a manganese steel material.

[0035] Experiment: The manganese steel materials obtained in Examples 1-3, Comparative Examples 1-3 and the austenitic manganese steel in Example 1 were taken to prepare samples, and their properties were tested respectively and the test results were recorded: Hardness test: Use electric spark cutting to cut the sample, and use Vickers hardness tester to test its surface hardness. The sample size is 20mm×20mm×10mm. Wear resistance test: Use a wear tester to detect the wear mass loss of the sample, and the wear time is 3h; Thermal oxidation performance test: The weight gain method is used to test the oxidation resistance of the sample at 550°C, and the weight gain of the sample after 20 hours is used as the experimental index; Fatigue resistance test: The micro crack observation method is used to compare the hot and cold fatigue performance at 700-25℃, and the number of surface cracks on the sample after 20h is used as the experimental index; Corrosion resistance test: The electrochemical test system was used with three electrodes, platinum as the auxiliary electrode, saturated calomel as the reference electrode, and 3.5wt% sodium chloride solution as the electrolyte to perform potentiodynamic polarization curve test. The scanning speed was 0.001V / s, the scanning voltage range was -0.5V to 0.5V, and the scanning frequency was 10 -2 ~10 5 Hz.

[0036]

[0037] According to the data in the above table, we can clearly draw the following conclusions: The manganese steel materials obtained in Examples 1-3, the manganese steel materials obtained in Comparative Examples 1-3 and the austenitic manganese steel in Example 1 are compared. The test results show that: Compared with the austenitic manganese steel in the comparative example and Example 1, the manganese steel materials obtained in Examples 1-3 have higher hardness, and lower wear, fatigue cracking, oxidation weight gain and self-corrosion current data, which fully demonstrates that the present invention achieves improvements in the hardness, wear resistance, resistance to cold and hot fatigue, thermal oxidation and corrosion resistance of manganese steel materials.

[0038] Compared with Example 1, no vapor deposition process is set in Comparative Example 1; no molybdenum infiltration and vapor deposition process is set in Comparative Example 2; no molybdenum infiltration and vapor deposition process is set in Comparative Example 3, and no aluminum nitride composite powder is added in the laser cladding process. The hardness of the manganese steel material obtained in Comparative Examples 1-3 decreases, and the wear, fatigue cracks, oxidation weight gain and self-corrosion current data deteriorate. It can be seen that the setting of the manganese steel material process and the components used in the present invention can promote the comprehensive improvement of its hardness, wear resistance, resistance to cold and hot fatigue, thermal oxidation and corrosion resistance.

[0039] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing thermally conductive austenitic manganese steel containing molybdenum, characterized in that: Including the following processes: Pig iron and pure iron are mixed and smelted; ferrochrome, ferromanganese, ferromolybdenum, ferrotitanium, ferroniobium and chromium nitride are added and smelted to form molten steel; the steel is taken out of the furnace and poured to obtain a billet; and austenitic manganese steel is obtained by heat treatment.

2. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 1, characterized in that: The austenitic manganese steel includes the following mass components: carbon: 1.2-1.5%, manganese: 6-9%, molybdenum: 1-2%, chromium: 2-4%, silicon: 0.8-1.0%, nitrogen: 0.1-0.5%, titanium: 0.06-0.10%, niobium: 0.05-0.07%, phosphorus ≤0.07%, sulfur ≤0.04%, and the balance is iron.

3. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 1, characterized in that: The furnace temperature is 1520~1550℃, and the pouring temperature is 1370~1420℃.

4. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 1, characterized in that: The process conditions of the heat treatment are: heating to 650-700°C at a heating rate of 50-100°C / h, keeping warm for 1-3h; then heating to 1050-1110°C at a heating rate of 100-150°C / h, keeping warm for 90-100min; and then water cooling.

5. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 1, characterized in that: After heat treatment, molybdenum infiltration and vapor deposition are performed in sequence to form a molybdenum layer; The process conditions of molybdenum diffusion are as follows: the source electrode is pure molybdenum, the inter-electrode spacing is 18mm, the source voltage is 650V, the source current is 1.4-1.6V, the cathode voltage is 400V, the cathode current is 3.8-4.0A, the temperature is 940-960℃, the atmosphere is argon, the working pressure is 35Pa, and after sputtering for 1-3h; the passive electrode sputtering is carried out under the mask for 30-90min; The process conditions of vapor deposition are: using molybdenum hexafluoride and hydrogen as raw materials, the deposition temperature is 1000-1100°C, the pressure is 2.0-2.7 kPa, and the duration is 90-120 minutes.

6. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 5, characterized in that: After vapor deposition, the alloy powder is used to laser clad the austenitic manganese steel to form a cladding layer; The process conditions of laser cladding are: laser power 1150~1250W, scanning speed 3.5~4.5mm / s, powder feeding speed 7.0~8.0g / min; laser spot diameter 1.5mm, overlap rate 60%, defocus amount 15mm, powder feeding gas and shielding gas are argon.

7. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 6, characterized in that: The alloy powder is Ni60 alloy powder and aluminum nitride composite powder, and the volume ratio is (5-7): (3-5).

8. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 7, characterized in that: The Ni60 alloy powder comprises the following components by mass: 0.6-1.0% carbon, 3.0-4.5% silicon, 14-17% chromium, 2.5-4.5% boron, less than 15% iron, 0.04-0.07% lanthanum, and the balance is nickel.

9. The method for preparing a thermally conductive austenitic manganese steel containing molybdenum according to claim 7, characterized in that: The aluminum nitride composite powder is prepared by the following process: Aluminum nitride, titanium powder and copper powder are mixed, vacuum ball milled at 200-250 r / min for 10-12 hours, and then spark plasma sintered. The sintering temperature is 950-970°C, the heating rate is 100°C / min, the loading pressure is 50 MPa, and the sintering time is 10-12 minutes.

10. A thermally conductive austenitic manganese steel containing molybdenum element obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • An austenite alloy steel material used for an internal combustion engine and a preparation method of the alloy steel material

    CN103614659A

  • Molybdenum-containing high-heat-conduction austenite wear-resisting manganese steel and preparation method thereof

    CN105088083A

  • Copper bearing nano-phase strengthened medium manganese steel and preparation method thereof

    CN106834942A

  • High-purity manganese13 high manganese steel

    CN109487037A

  • High-manganese high-carbon weldable metal ceramic block, enhanced roller sleeve thereof and preparation method

    CN111621721A